2008
DOI: 10.1182/blood-2007-04-087734
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively activated STAT3 promotes cell proliferation and survival in the activated B-cell subtype of diffuse large B-cell lymphomas

Abstract: Diffuse large B-cell lymphoma (DLBCL) consists of at least 2 phenotypic subtypes; that is, the germinal center B-celllike (GCB-DLBCL) and the activated Bcell-like (ABC-DLBCL) groups. It has been shown that GCB-DLBCL responds favorably to chemotherapy and expresses high levels of BCL6, a transcription repressor known to play a causative role in lymphomagenesis. In comparison, ABC-DLBCL has lower levels of BCL6, constitutively activated nuclear factor-B, and tends to be refractory to chemotherapy. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
263
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(296 citation statements)
references
References 54 publications
28
263
3
2
Order By: Relevance
“…40 In our FL collective, the expression of pSTAT5 correlated with higher amounts of tumor-infiltrating regulatory T cells, which are also known to be associated with favorable outcomes. 25 Finally, we confirmed the prognostic importance of pSTAT3 in activated B-cell-like DLBCL, which was recently observed by others, 18 as our own nongerminal center DLBCL expressing pSTAT3 had also an inferior disease-specific survival, again indicating the oncogenic potential of pSTAT3.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…40 In our FL collective, the expression of pSTAT5 correlated with higher amounts of tumor-infiltrating regulatory T cells, which are also known to be associated with favorable outcomes. 25 Finally, we confirmed the prognostic importance of pSTAT3 in activated B-cell-like DLBCL, which was recently observed by others, 18 as our own nongerminal center DLBCL expressing pSTAT3 had also an inferior disease-specific survival, again indicating the oncogenic potential of pSTAT3.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to others, we observed preferential expression of pSTAT3 in ALCL, 16,17 HL 35 (but not in NLPHL) and nongerminal center DLBCL. 18 Our PTCLs also preferentially expressed pSTAT3. As in ALK1 þ ALCL, NPM-ALK constitutively activates STAT3 by increased protein phosphorylation and increased transcription/stabilization of STAT3 mRNA and ALCLs overexpress JAK3, 16 our observed high predominance of pSTAT3, despite low expression of pJAK2 was expected.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…12,13 Recently, it has been reported that STAT3 is overexpressed in ABC-type DLBCL human cell lines. 14,15 The role of pSTAT3 as a prognostic factor in DLBCL patients treated with R-CHOP-based therapies is unknown.Translocations involving the MYC gene at 8q24 are associated with Burkitt lymphoma. 16 Moreover, MYC translocations have been reported to occur in DLBCL with a frequency of 5%-10%.…”
mentioning
confidence: 99%